Frequency of Systemic Lupus Erythematosus Was Decreasing Among Hospitalized Patients From 2013 to 2017 in a National Database in China - Tan, Ying; Yu, Feng; Long, Jianyan; Gan, Lanxia; Wang, Haibo; Zhang, Luxia; Zhao, Minghui (Frontiers in Medicine, 2021)
Backgrounds: Limited data was reported for the frequency of SLE in China. The aim of this study was to investigate the frequency, geographical, and ethnic distributions of hospitalized SLE patients with data from the Hospital Quality Monitoring System (HQMS) in China. Methods: Hospitalized patients were investigated from a national inpatient database covering 46.0% of tertiary hospitals in China from 2013 to 2017. Data regarding the diagnosis of SLE were extracted based on ICD-10 codes. We collected and analyzed data from the front page of the records of inpatients, including frequency, demographic characteristics, and geographic distributions of SLE. Results: Among 158.3 million inpatients attended during the study period, 0.31% (491, 225) were diagnosed with SLE. The frequency of SLE decreased during the study period (from 0.30% in 2013 to 0.27% in 2017). The frequency of SLE increased with latitude (0.21% in northern China and 0.39% in southern China in 2017). Hospitalizations mostly occurred in winter (31.24%). The Li population had the highest frequency of patients with SLE (0.76%). The all-cause in-hospital mortality rate of SLE decreased from 0.74% (255/34,746) in 2013 to 0.54% (295/54,168) in 2017. The percentage of SLE patients with infections increased from 3.14% in 2013 to 4.72% in 2017. The percentage of SLE patients with tumors and thrombosis also increased slightly from 0.85 and 1.43% in 2013 to 1.27 and 2.45% in 2017, respectively. Conclusion: This study provided epidemiological information of SLE in hospitalized patients in China for the first time. An ethnic and spatial clustering trend of SLE was observed.